Exploring study dropout in drug trials for adults with PTSD: insights from a conventional and individual participant data meta-analysis - Simonne L. Wright; Anna Kessler; Marit Sijbrandij; Eirini Karyotaki; Pim Cuijpers; Jonathan Bisson; Kathleen Brady; Sheila M. Dowd; Boadie W. Dunlop; Mark H. Pollack; Barbara O. Rothbaum; Soraya Seedat (European Journal of Psychotraumatology)
Background: Dropout rates and factors contributing to dropout in drug and placebo groups in pharmacotherapy trials for posttraumatic stress disorder (PTSD) are not well understood.Objective: This study aimed to examine differences in all-cause study dropouts between drug and placebo groups, using conventional meta-analysis and an exploratory predictor analysis of individual participant data from three trials.Method: We included randomized controlled trials (RCTs) of adults with PTSD, comparing drug monotherapy with placebo. Forty-three RCTs (n = 4829) were included in a conventional meta-analysis. Additionally, we conducted a small exploratory predictor analysis including participant-level data from three RCTs (n = 246).Results: In the conventional meta-analysis, study dropout was marginally lower in the drug relative to the placebo group, but the difference was not significant, RR = 0.92, 95% CI [0.83, 1.02], p = .099. Drug class, dosing regimen, population, study duration, or gender were not related to dropout.In the exploratory predictor analysis, study dropout did not differ significantly between drug and placebo groups (p = .617). In the drug group, gender was a significant predictor for dropout, with males having higher dropout rates (p = .046). When controlling for baseline PTSD symptom severity, gender was no longer a statistically significant predictor (p = .051). None of the other predictors in drug, placebo, and combined group analyses were significant in predicting drop-out.Conclusions: This study demonstrated that study dropout rates in monotherapy pharmacotherapy RCTs for PTSD do not significantly differ between drug and placebo groups. These findings underscore the need for further research to identify the factors contributing to dropout in PTSD pharmacotherapy trials and to develop tailored treatment adherence strategies. Additionally, they highlight the importance of pooling participant-level data to facilitate more comprehensive and granular analyses in future research.